Integration of woodland caribou habitat management and forest management in northern Ontario - current status and issues - Armstrong, Ted (E.R) (Rangifer, 1998)
Woodland caribou {Rangifer tarandus caribou) range across northern Ontario, occurring in both the Hudson Bay Lowlands and the Boreal Forest. Woodland caribou extend south well into the merchantable forest, occurring in licensed and/or actively managed Forest Management Units (FMU's) across the province. Caribou range has gradually but continuously receded northward over the past century. Since the early 1990's, the Ontario Ministry of Natural Resources (OMNR) has been developing and implementing a woodland caribou habitat management strategy in northwestern Ontario. The purpose of the caribou habitat strategy is to maintain woodland caribou occupancy of currently occupied range in northwestern Ontario. Long-term caribou habitat needs and predator-prey dynamics form the basis of this strategy, which requires the development of a landscape-level caribou habitat mosaic across the region within caribou range. This represents a significant change from traditional forest management approaches, which were based partially upon moose (Alces alces) habitat management principles. A number of issues and concerns regarding implications of caribou management to the forest industry are being addressed, including short-term and long-term reductions in wood supply and wood quality, and increased access costs. Other related concerns include the ability to regenerate forests to pre-harvest stand conditions, remote tourism concerns, implications for moose populations, and required information on caribou biology and habitat. The forest industry and other stakeholders have been actively involved with the OMNR in attempting to address these concerns, so that caribou habitat requirements are met while ensuring the maintenance of a viable timber industry, other forest uses and the forest ecosystem.